Nephroprotective activity of naringin against chemical-induced toxicity and renal ischemia/reperfusion injury: A review - Negin Amini; Maryam Maleki; Mohammad Badavi (Avicenna Journal of Phytomedicine, 2022)
Objective: The kidney is well-known as the vital organ which is responsible for maintaining body homeostasis and secretion of toxic metabolites. Renal injury is accompanied by oxidative stress which results in cellular apoptosis, lipid peroxidation, and reduction of antioxidant levels. Plant extracts and their phytoconstituents, owing to free radical scavenging properties, seem to be valuable against modern synthetic and chemical drugs. Naringin is a flavonoid present in citrus fruits with pharmacologic effects including antioxidant, anti-inflammatory, and anti-apoptotic properties. This review summarizes the renoprotective effects of naringin and discusses mechanisms of its action against renal injury.Materials and Methods: For this paper, original subject-related articles published up to October 2020 have been reviewed in the databases, including PubMed, Scopus, and Web of Science, and Google Scholar.Results: Naringin increases antioxidant enzyme activity, and glutathione content, reduces lipid peroxidation and inhibits inflammatory cytokines. In the molecular investigation, naringin activates the Nrf-2 signaling, prevents apoptosis signaling, and inhibits the autophagy pathway. Besides, naringin could protect the kidney through modulating microRNA-10a in the kidney tissue in an acute kidney injury model.Conclusion: This review recommends that naringin can be considered a promising candidate to treat kidney dysfunction induced by oxidative stress in the future.